A Systematic Review and Meta-Analysis of The Long-Term Outcomes of Acute Myocardial Infarction in Preexisting Coronary Artery Ectasia - Magdi, Mohamed; Mostafa, Mostafa Reda; Alabdouh, Ahmad; Hassan, Yossef; Abdelazeem, Basel; Ismayl, Mahmoud; Mohamed, Sarah; Al Ali, Omar; Baibhav, Bipul; Mamas, Mamas (International Journal of Innovative Research in Medical Science, 2022)
Background: Coronary artery ectasia is associated with an increased risk of acute myocardial infarction. This meta-analysis evaluates outcomes following acute myocardial infarction in patients with preexisting coronary artery ectasia. Methods: This meta-analysis was conducted according to PRISMA guidelines. A search strategy was designed to utilize PubMed/Medline, EMBASE, and Google scholar for studies showing the outcomes of acute myocardial infarction in patients with coronary artery ectasia from inception to February 10, 2022. We reported effect sizes as odds ratio (OR) with a 95% confidence interval (CI). We used I2 statistics to estimate the extent of unexplained statistical heterogeneity: I2 greater than 50% was considered a high degree of between-study statistical heterogeneity. Results: Of 217 studies initially identified, 7 studies comprising 13499 patients were included in the final analysis. There was no significant difference between patients with coronary ectasia and patients without coronary ectasia in terms of all-cause mortality (OR 0.95; 95% CI 0.58 to 1.56; p = 0.79; I2=0%), MACE (OR 4.04; 95% CI 0.34 to 47.57; p = 0.17; I2=95%), myocardial reinfarction (OR 2.13; 95% CI 0.83 to 5.47; p = 0.08; I2=59%), target vessel revascularization (OR 1.31; 95% CI 0.69 to 2.48; p = 0.21; I2=0%), or requiring mechanical supportive devices (OR 1.32; 95% CI 0.22 to 7.83; p = 0.57; I2=56%). Conclusion: Acute myocardial infarction in the presence of coronary artery ectasia is not linked to an increased risk of death, major cardiovascular events, myocardial infarction, or the need for mechanical circulatory support.